Health-related quality of life of patients with multiple sclerosis in China: a national online survey - Xinyi Song; Xuanqi Qiao; Yusheng Jia; Hainan Li; Pei Wang; Min Hu (Health and Quality of Life Outcomes)
Abstract Background To measure and value the health-related quality of life (HRQOL) of Chinese Multiple sclerosis (MS) patients, and to explore the influencing factors. Methods A national online survey amongst the patients was conducted in July 2022. Information on patient demographics, clinical characteristics (MS subtype and disability status), and the HRQOL measured by EQ-5D-5L were collected. Disability status was classified based on the self-reported Expanded Disability Status Scale (EDSS). Both the Tobit and logistic regression models were adopted to assess the impact of clinical characteristics on HRQOL with the adjustment of demographic characteristics. Results A total of 733 eligible patients (mean age 34.31 years; 67.7% females) were included in the analysis. The mean EQ-5D-5L health utility score (HUS) and VAS score were 0.73(SD:0.29) and 68.7(SD:23.9), respectively. MS patients reported a high prevalence of health problems in all the EQ-5D dimensions, ranging from 25.6% (self-care) to 74.9% (anxiety/depression). According to Tobit regression analyses, secondary progressive MS was associated with lower VAS compared to relapsing–remitting MS. Worse disability status measured by EDSS was related to the lower HUS and VAS scores. Demographic characteristics including younger age, higher education level, and employment were also identified as protective factors of the patients’ HRQOL. Conclusions This study assessed HRQOL of Chinese MS patients using the EQ-5D-5L. Our finding revealed that MS subtypes and disability status are the most important factors affecting their HRQOL.